A quantitative study of OH and NO concentration of a premixed laminar kerosene flame using a flat-flame burner at atmospheric pressure - Shi, Si; Hughes, Kevin J.; Pourkashanian, Mohamed (Frontiers in Fuels, 2024)
In the context of global warming and the increasing demands for the application of sustainable fuels, measurements of a variety of experimental targets under a wide range of conditions are crucial to improving the fundamental understanding of real jet fuels and developing quality kinetic mechanisms for large hydrocarbons. Planar laser-induced fluorescence (PLIF) is an effective approach to investigate concentrations of important species of a given flame while quantifying the fluorescence image remains a great challenge with significant uncertainties. This investigation aims to improve the fundamental understanding of the oxidation of kerosene-based mixtures at two equivalence ratio conditions. Two gas fuels are utilized as the reference for the quantitative studies. For each flame condition, relative OH and NO quantities and temperature profiles were measured by applying the PLIF and coated fine wire type R Pt/Pt-Rh thermocouples, respectively. The converted OH and NO results were subsequently compared with the simulation by using ANSYS Chemkin Pro.